The Institute of Physical Medicine and Rehabilitation, Hospital das Clínicas University of São Paulo School of Medicine comprehensive rehabilitation program for elderly people with knee osteoarthritis - Imamura, Marta; Shinzato, Gilson T.; Sugawara, André T.; Uchiyama, Sabrina Saemy Tome; Matheus, Denise; Simis, Marcel; Ayres, Denise Vianna Machado; dos Santos, Artur C. A.; Assone, Tatiane; Ramos, Vinícius Delgado; Fregni, Felipe; Battistella, Linamara R. (Frontiers in Medicine, 2022)
Background: Knee osteoarthritis (OA) is a leading cause of disability in the elderly population. Chronic disabling pain is associated with maladaptive neuroplastic changes in brain networks, commonly associated with central sensitization. The main clinical features of nociplastic pain conditions include combined peripheral and central sensitization, and it is crucial to recognize this type of pain, as it responds to different therapies than nociceptive and neuropathic pain. Objective: To report the effect of the Institute of Physical Medicine and Rehabilitation (IMREA) comprehensive rehabilitation program to reduce pain and to improve functioning in elderly people with knee OA, under the DEFINE cohort. Methods: This is a retrospective observational cohort of 96 patients with knee OA, recruited from October 2018 to December 2019. All patients were evaluated by a trained multidisciplinary team using the Kellgren Lawrence classification, bilateral knee ultrasonography, the visual analogue scale (VAS), the Western Ontario and McMaster Universities Arthritis Index (WOMAC) pain, rigidity and difficulty scores, the Timed Up and Go Test (TUG), 10-meter and 6-minute walking test (10MWT and 6MWT), Berg Balance Scale, isokinetic dynamometry for knee extension and flexion strength, and pain pressure thresholds. The rehabilitation program included paraspinous lidocaine blocks, focal extracorporeal shockwaves combined with radial pressure waves and functional electrical stimulation according to individual needs. The baseline was compared with the treatment results with a paired t-test. Results: The study sample is composed of 96 participants, mostly females (n=81, 84.38%), with bilateral osteoarthritis (n=91, 94.79%), and a mean age of 68.89 (SD 9.73) years. Functional improvement was observed in TUG, 6-mwt, right knee flexion strength, WOMAC rigidity and difficulty domains. Pain was reduced from baseline as measured by WOMAC pain domain, VAS for both knees, and SF-36 pain domain. Pressure pain threshold was modified above the patella, at the patellar tendons, left S2 dermatome, and L1-L2. Conclusions: The IMREA comprehensive rehabilitation program improved functioning and reduced disabling pain in elderly people with knee OA. We highlight the relevance and discuss the implementation of our intervention protocol. Although this is an open cohort study, it is important to note the significant improvement with this clinical protocol.